Structural and ultrastructural in situ analyses of preantral follicles in adult female buffaloes - Carvalho, F. C.A. [UNESP]; Oba, E. [UNESP]; Camargos, A. S. [UNESP]; Ferreira, J. C.P. [UNESP]; Magalhães, L. C.O. [UNESP] (My University, 2010)
This research aimed to perform structural and ultrastructural in situ analyses of preantral buffalo follicles, estimate average diameter of the follicles, oocytes and nuclei as well as classify granulosa cells into follicular categories. Six crossbred Murrah-Mediterranean buffalo ovaries (one ovary from each buffalo cow) were processed, stained and subjected to histological examination. Preantral follicles were classified as primordial, transitional, primary or secondary. Follicular quality was evaluated according to their basal membrane integrity, cell density, presence or absence of pyknotic bodies and oocyte integrity. For the morphological quality evaluation, follicles were classified as normal, degenerated Type I, or degenerated Type II. Only normal follicles underwent ultrastructural analysis in a transmission electron microscope. Morphometric analysis showed that primordial, transitional, primary and secondary follicles have an average diameter of 32.67; 35.05; 39.32 and 83.08 m, oocyte diameter of 26.34; 26.88; 28.04 and 40.87 m, and nucleus diameter of 10.28; 10.57; 12.10 and 12.88 m, respectively. Buffalo preantral follicles presented either spherical or oval oocytes in the ultrastructural analysis, with eccentric nucleus, and organelles that were uniformly distributed in the cytoplasm, with a large number of vacuoles. Transitional and primary follicles revealed a large amount of lipid droplets that were usually associated with smooth endoplasmic reticulum, between the granulosa cells.
Keywords: Buffalo cows; Histology; Preantral follicles; Ultrastructural